Ayurvedic overview of Aragwadha (Cassia fistula Linn.). - Lakhran, Ashok Kumar; Kotecha, Mita (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is not only a life science but also a spiritual science that deals with how to maintain a healthy life and prevent the onset of disease. In Dravyaguna, a branch of ayurveda many drugs are used in many diseases. One of these dravyas is Aragwadha, Latin named Cassia fistula Linn. of the Leguminosae family. In Ayurveda it is called Rajvruksha due to its beautiful flowers. It is a common plant in India and also known as Golden Shower, traditionally its various parts, including the bark, leaves, flowers, and fruits are used for various medicinal and therapeutic purposes. This review aims to provide a comprehensive overview of the medicinal properties and therapeutic applications of Aragwadha, based on available scientific literature and traditional knowledge.